PERAN ’URF SEBAGAI PENENTU HUKUM PERSPEKTIF SOSIOLOGI HUKUM ISLAM - Syarif, Muhammad Isra; Misbahuddin, Misbahuddin; Lutfi, Mukhtar (Fakultas Syariah (Syari'ah Faculty ), 2024)
al-'Urf as a source of law has a role in social dynamics. al-'Urf can be used as a legal basis for certain conditions. This research is qualitative research with the type of library research and uses a sociological normative approach method. The results of this research show that al-'Urf is what is considered good and right by humans in general and is done repeatedly so that it becomes a habit. al-'Urf is often equated with custom, but there is a difference, namely that the term custom only emphasizes the repetitive aspect of work, while al-'Urf only looks at the perpetrator. As for the similarities, adat and al-'Urf are work that has been accepted by common sense, embedded in the heart, carried out repeatedly and in accordance with the character of the perpetrator. al-‘Urf contributes to the flexibility of Islamic law and allows law to adapt to social changes without losing its fundamental values. This is in accordance with the fiqh rule